Factors Influencing Stent Failure in Chronic Total Occlusion Coronary Intervention - Kalaivani Mahadevan; Claudia Cosgrove; Julian W Strange (Interventional Cardiology: Reviews, Research, Resources)
Stent failure remains one of the greatest challenges for interventional cardiologists. Despite the evolution to superior second- and third-generation drug-eluting stent designs, increasing use of intracoronary imaging and the adoption of more potent antiplatelet regimens, registries continue to demonstrate a prevalence of stent failure or target lesion revascularisation of 15–20%. Predisposition to stent failure is consistent across both chronic total occlusion (CTO) and non-CTO populations and includes patient-, lesion- and procedure-related factors. However, histological and pathophysiological properties specific to CTOs, alongside complex strategies to treat these lesions, may potentially render percutaneous coronary interventions in this cohort more vulnerable to failure. Prevention requires recognition and mitigation of the precipitants of stent failure, optimisation of interventional techniques, including image-guided precision percutaneous coronary intervention, and aggressive modification of a patient’s cardiovascular risk factors. Management of stent failure in the CTO population is technically challenging and itself begets recurrence. We aim to provide a comprehensive review of factors influencing stent failure in the CTO population and strategies to attenuate these.